Uji Pertumbuhan Beberapa Nomor Isolat Calon Bibit Sebar F3 Jamur Merang (Volvariella volvaceae) FAPERTA UNSIKA Menggunakan Media Tumbuh Jerami Padi - Amelia, Firda Rizky; Lestari, Ani; Supriadi, Devie Rienzani (JURNAL AGROPLASMA, 2023)
Superior seeds are one of the factors in determining the success of straw mushroom (Volvariella volvaceae) cultivation. Pure culture of straw mushroom can be obtained through several stages, including pure culture culture or F0, then from F0 it is sub-cultured into F1, F2, F3 and F4 seeds. The purpose of this study was to obtain one of the isolate numbers for the candidate seedling F3 which gave the best growth using rice straw media. The research was conducted in a farmer's mushroom house located in the village of Pasirmulya, Majalaya, Karawang Regency. The research will be carried out for approximately 2 months from December to January 2023. The research method used is a randomized block design (RBD) with 5 repetitions. There were 7 repetitions, namely A (F3 FP White), B (F3 FP Semi), F3 Clones 11, F3 Clones 12, F3 Clones 13, F3 Clones 14 and F3 Clones 15. The effect of treatment was analyzed using analysis of variance and if the F test was significant at 5% level, then to find out which treatment gave the best results it was continued with the DMRT (Duncan Multiple Range Test) at 5% level. The results showed that there was a significant effect on the growth of several numbers of candidate isolates for spreading F3 mushroom (Volvariella volvaceae) Faperta Unsika on the use of rice straw media. Treatment E (Clone 13) gave the highest total weight of one kumbung of 1828.80 g, when converted the yield in one kumbung became 63.80 kg, the average fruit weight per plot was 135.732 g and the average harvest intensity of one growing season during 14,400 days.Â Key Words:Isolate F3 Faperta Unsika,Straw,Straw Mushroom, Clone 13